Web and user frontend for CleverMiner - Zedníčková, Miriam (2025)
This thesis focuses on the design and implementation of a user-friendly web frontend application for CleverMiner, a data mining Python package. The main objective is to create an intuitive interface accessible to users without programming skills, enabling them to leverage advanced data mining procedures such as CF-Miner. The minimalistic backend is developed using FastAPI to provide efficient and scalable API services. Beyond the design and development of the frontend, this work also explores various distribution strategies, including containerization with Docker and packaging as a desktop application via Electron. These approaches aim to ensure flexible installation options suitable for both server environments and local user workstations.